From Meals to Meaning: Applying Human-Centered Strategies for Sustainable Competitive Advantage in the Food Sector - Octhaviani, Ariska; Nurmasari, Nuraini Desty (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose–This study aims to enhance the business performance of Pecel Lesehan Pak Kasto by developing a human-centered marketing strategy that addresses evolving customer needs and expectations in the increasingly competitive culinary MSME sector. Design/Methodology/Approach–This research adopts a design thinking approach consisting of five stages: empathize, define, ideate, prototype, and testing. Through a human-centered perspective, customer insights were explored to identify expectations beyond functional food consumption and to formulate appropriate marketing strategies. Findings–The findings reveal that customers seek not only food but also meaningful culinary experiences. Based on these insights, the proposed marketing strategy focuses on strengthening brand identity, improving service quality, and creating distinctive culinary experiences. The implementation of this strategy enhances brand awareness, customer satisfaction, and customer loyalty. The results also suggest that culinary MSMEs should continuously update their understanding of customer needs and adapt to changing consumer trends to maintain sustainable competitive advantages. Originality/Value–This study contributes to marketing literature by demonstrating the application of a human-centered design thinking framework in developing marketing strategies for a traditional culinary MSME. It provides practical value by showing how empathy-driven marketing strategies can strengthen customer relationships, improve business performance, and foster long-term competitiveness.